Understanding climate change through the eyes of children: a qualitative study with secondary school students - Özcan Tan, Ümmühan; Demirkaya, Hilmi (Frontiers in Psychology, 2025)
This study examined secondary school students’ perceptions of climate change, their levels of interest, and their comprehension of the concept, as well as their views on its causes, perceived effects, and suggestions for enhancing sustainability education in schools. A qualitative methodology was employed to capture the students’ authentic perspectives and meaning-making processes. Semi-structured interviews were conducted with 37 students in grades 6 and 7 attending a public middle school in southern Turkey. Thematic analysis revealed that although most participants expressed concern and curiosity about environmental issues, their understanding of climate change was often fragmented or media-influenced by media sources. Students primarily associated climate change with observable environmental changes, such as rising temperatures and natural disasters, and less frequently with human activities or with policy implications. Notably, the participants emphasized the need for more engaging and practical learning experiences, including outdoor projects, environmental clubs, and media literacy activities within the school curriculum. These findings underscore the importance of enhancing climate literacy and sustainability education in schools, with a focus on integrating critical media awareness and participatory learning opportunities. The study concludes with recommendations for improving environmental education through student-centered and enquiry-based teaching methods.